COVID-19 vaccination before or during pregnancy results in high, sustained maternal neutralizing activity to SARS-CoV-2 wild-type and Delta/Omicron variants of concern, particularly following a booster dose or infection - Mahyuddin, Aniza P. (2024)
Objectives: To investigate multi-dose and timings of COVID-19 vaccines in preventing antenatal infection. Design: Prospective observational study investigating primary vaccinations, boosters, antenatal COVID-19 infections, neutralizing antibody (Nab) durability, and cross-reactivity to Delta and Omicron variants of concern (VOCs). Results: Ninety-eight patients completed primary vaccination prepregnancy (29.6%) and antenatally (63.3%), 24.2% of whom had antenatal COVID-19, while 7.1% were unvaccinated (28.6% had antenatal COVID-19). None had severe COVID-19. Prepregnancy vaccination resulted in vaccination-to-infection delay of 23.3 weeks, which extended to 45.2 weeks with a booster, compared to 16.9 weeks following antenatal vaccination (P < 0.001). Infections occurred at 26.2 weeks gestation in women vaccinated prepregnancy compared to 36.2 weeks gestation in those vaccinated during pregnancy (P < 0.007). The risk of COVID-19 infection was higher without antenatal vaccination (hazard ratio [HR] 14.6, P = 0.05) and after prepregnancy vaccination without a booster (HR 10.4, P = 0.002). Antenatal vaccinations initially led to high Nab levels, with mild waning but subsequent rebound. Significant Nab enhancement occurred with a third-trimester booster. Maternal-neonatal Nab transfer was efficient (transfer ratio >1), and cross-reactivity to VOCs was observed. Conclusion: Completing vaccination during any trimester delays COVID-19 infection and maintains effective neutralizing activity throughout pregnancy, with robust cross-reactivity to VOCs and efficient maternal-neonatal transfer.